Flexural Behavior of Fiber-Reinforced Self-Stressing Concrete T-Shaped Composite Beams - Boxin Wang; Ruichang Fang; Qing Wang (Advances in Civil Engineering)
Given the excellent crack resistance performance of steel fiber-reinforced self-stressing concrete (SFRSSC), the bending performance of some composite beams with SFRSSC laminated layers was studied. The experiment conducted in this study comprised a single-span composite beam test (including 3 test beams) and a two-span continuous composite beam test (including 2 test beams). All the test beams were T-shaped. The cracking load, yielding load, and ultimate load of all the test beams were recorded and comparatively analyzed. Experimental results showed that the cracking load of the test beam with an SFRSSC laminated layer is significantly increased. Mechanical analysis and numerical simulation of the test beams were conducted, and the obtained results agreed well with the experimental results. The composite beams under different working conditions were also numerically simulated. Through the simulation, reasonable ranges of precompressive stress and length of the SFRSSC laminated layer at intermediate support of continuous composite beam were obtained.